2022
DOI: 10.1038/s41598-022-19842-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrroloquinoline quinone on noise-induced and age-related hearing loss in mice

Abstract: We investigated whether the oxidoreductase cofactor pyrroloquinoline quinone (PQQ) prevents noise-induced and age-related hearing loss (NIHL and ARHL) in mice. To assess NIHL, 8 week-old mice with and without PQQ administration were exposed to noise for 4 h. PQQ was orally administered for one week before and after noise exposure and subcutaneously once before noise exposure. For ARHL evaluation, mice were given drinking water with or without PQQ starting at 2 months of age. In the NIHL model, PQQ-treated mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Research has shown that PQQ improves cognitive brain function for memory learning ability in aged mice ( Yamada et al, 2020 ) and for composite and verbal memory in older adults ( Tamakoshi et al, 2023 ). Additionally, other studies in mice have demonstrated that the antioxidant effects of PQQ ameliorate age-related hearing loss ( Gao et al, 2022 ), prevent estrogen deficiency-induced osteoporosis ( Geng et al, 2019 ), and protect against skin aging ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that PQQ improves cognitive brain function for memory learning ability in aged mice ( Yamada et al, 2020 ) and for composite and verbal memory in older adults ( Tamakoshi et al, 2023 ). Additionally, other studies in mice have demonstrated that the antioxidant effects of PQQ ameliorate age-related hearing loss ( Gao et al, 2022 ), prevent estrogen deficiency-induced osteoporosis ( Geng et al, 2019 ), and protect against skin aging ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting brain functions, PQQ has an inhibitory effect on fat accumulation during high-fat diet consumption in animal studies (44,45), and PQQ was shown to improve hearing loss (46) and extend lifespan (47). Therefore, it may be effective in improving fat metabolism and fighting age-related disorders.…”
Section: Conflict Of Interestmentioning
confidence: 99%